The Impact of Corporate Reputation on Firm Risk: A Panel Data Analysis of Spanish Quoted Firms. (21st September 2011) - Delgado‐García, Juan Bautista; de Quevedo‐Puente, Esther; Díez‐Esteban, José María
Abstract : Researchers have traditionally addressed the influence of corporate reputation on firm performance, but have not considered the influence of corporate reputation on firm risk. This research develops hypotheses regarding the opposing influence of corporate reputation on a firm's systematic risk, unsystematic risk and total risk, as well as the moderation effect of firm size and industry concentration. Using a panel data method, these relationships are analysed, controlling for the effects of endogeneity, for a sample of Spanish quoted firms in the period 2001–2007. Specifically, two complementary analyses are performed. The first distinguishes firms included and not included in the MERCO index of the most reputable firms. The second analyses the impact of corporate reputation for the sub‐sample of most reputable firms. Being reputable reduces a firm's unsystematic risk and total risk, but increases systematic risk. In addition, firm size weakens these influences of corporate reputation on firm risk. However, among the most reputable firms, differences in reputation score have a lower effect on risk. Specifically, the corporate reputation level only influences firm unsystematic risk. It seems that what matters is not the degree of corporate reputation, but whether being or not being reputable is the question in terms of risk.